2011
DOI: 10.1111/j.1365-263x.2011.01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mode of delivery and feeding practices on acquisition of oral Streptococcus mutans in infants

Abstract: The causes for initial acquisition of oral S. mutans in infants were postnatal factors like feeding and oral hygiene practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
4
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
4
17
4
4
Order By: Relevance
“…A correlation between MS and social deprivation was found to depend on the caries status of the infants 19 . Although a correlation between breast feeding and MS was found in this study, other studies indicate no correlation between them 1 , and even present a preventive role in the colonization of MS 20 . A recent study did find that Lactobacilli colonized the oral cavity of breastfed infants significantly more frequently than formula-fed infants 21 .…”
Section: Discussioncontrasting
confidence: 94%
“…A correlation between MS and social deprivation was found to depend on the caries status of the infants 19 . Although a correlation between breast feeding and MS was found in this study, other studies indicate no correlation between them 1 , and even present a preventive role in the colonization of MS 20 . A recent study did find that Lactobacilli colonized the oral cavity of breastfed infants significantly more frequently than formula-fed infants 21 .…”
Section: Discussioncontrasting
confidence: 94%
“…Although studies have reported that gender is not significantly correlated with S. mutans colonization in infants, 23,24 our study showed that females more often displayed S. mutans colonization than males. Females tend to develop more quickly than males, with the former showing earlier tooth eruption patterns in China.…”
Section: Discussioncontrasting
confidence: 80%
“…11 Using a plated culture technique for S. mutans detection, a relatively higher proportion of full-term Australian infants, 34% (44/128), was S. mutans positive at 11-15 weeks 15 compared with our findings. Again, in a similar cohort of predentate infants, 60% (67/112), a higher proportion was positive for S. mutans at 6 months of age; the authors attributed the high proportions to their sample size and sensitivity of their culture media.…”
Section: Discussioncontrasting
confidence: 52%
“…A review of published studies concerning sources of colonization of MS in children concluded that mothers appear to be the primary source, 9 and breastfed infants were found at higher risk for oral MS compared with bottle-fed infants. 10,11 As an ancillary investigation within an ongoing clinical trial, we had the opportunity to examine oral MS status in 4-6-week-old predentate infants and their mothers. Therefore, the purpose of this study was to investigate the association of infant feeding method (breastfeeding versus formula feeding) with infant MS status, in the context of mother-infant pairs.…”
Section: Introductionmentioning
confidence: 99%